Health benefits of herbal extracts and beverages - Skrajda-Brdak, Marta Natalia (Journal of Education, Health and Sport, 2018)
Introduction: Herbs has been used for thousands of years mainly due to the high content of bioactive compounds. Predominant bioactive compounds of herb extracts and beverages are polyphenols, including phenolic acids and flavonoids. Data shows that antioxidant activity is mostly related to these compounds. Aim: The aim of this work was to provide an overview of health benefits of selected herbal extracts and beverages. Due to large amount of available herbs on the market, only four were chosen and described in details. Results: Based on literature data, depending on the type of the plant and its morphological part different activities occur. Also, the type of extractant and extraction is of great importance. Health benefits of white mulberry, milk thistle, dandelion and ST. John’s wort were described in details. It was indicated that white mulberry show hypoglycemic and hypolipidemic activity, milk thistle and dandelion can be used to treat liver disorders, while St. John’s wort can help with depression. Conclusions: Herbal extracts and beverages can be considered as nutraceuticals due to their positive effect on human health.